Curable composition and method for producing cured film

JP2025041297APending Publication Date: 2025-03-26KONICA MINOLTA INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023148490
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-26

Smart Images

  • Figure 2025041297000001_ABST
    Figure 2025041297000001_ABST
Patent Text Reader

Abstract

To provide a curable composition that can produce a cured film that has both followability to deformation of a base material and suppression of cracking near a cut portion, in particular, a cured film that suppresses a change in properties among base materials when a plurality of base materials is stacked and cut.SOLUTION: A content of a monofunctional polymerizable compound having a melting point of 25°C or less is 5 to 50 mass%, and a content of a polyfunctional polymerizable compound is 50 mass% or more and 95 mass% or less. When a nanoindentation evaluator is used to press an indenter into a cured film, which is obtained by curing a coating film with a thickness of 8 μm by irradiation with an active ray at a cumulative light amount of 400 mJ / m2, by 100 nm in the thickness direction, P1 is a load amount required for pressing, and P2 is a load amount after the pressing is maintained for 2 seconds, the cured film satisfies conditions (1) and (2): (1) P2 is 20 μN or less, and (2) A relaxation rate determined by an expression ((P1-P2) / P1×100) is 15% or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable composition and a method for producing a cured film. [Background technology]

[0002] A cured film formed by applying a curable composition containing a polymerizable compound and curing it by irradiation with actinic radiation has the characteristics of high film hardness and high scratch resistance. Therefore, the cured film formed from the curable composition is used in various fields such as images and various electronic devices.

[0003] On the other hand, a cured film formed from a curable composition does not easily deform when the substrate is deformed. Therefore, the cured film is easily broken during folding or other processes. Patent Document 1 describes a monofunctional monomer-rich curable composition that combines a monofunctional monomer having a high glass transition temperature (Tg) with a monofunctional monomer having a low Tg, as a curable composition that can improve the conformity to deformation of the substrate while maintaining the strength of the cured film. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-172841 A Summary of the Invention [Problem to be solved by the invention]

[0005] Patent Document 1 describes that the cured film obtained from the composition described in this document has both strength and ability to follow deformation of the substrate (stretchability). According to the study by the present inventors, the cured film obtained from the composition described in Patent Document 1 has the ability to follow deformation of the substrate, but on the other hand, when the substrate on which the cured film is formed (for example, a printed paper on which an image is formed) is cut, cracks tend to occur near the cut part. In particular, when multiple printed papers on which images are formed are stacked and cut, the quality of the cut part tends to differ between the top image and the second and subsequent images.

[0006] The present invention has been made in consideration of the above circumstances, and has an object to provide a curable composition capable of producing a cured film that is compatible with the deformation of a substrate and suppresses cracking near a cut portion, particularly a cured film that suppresses changes in quality between substrates when multiple substrates are stacked and cut. Another object of the present invention is to provide a method for producing a cured film using the curable composition. [Means for solving the problem]

[0007] In order to solve the above problems, one aspect of the present invention relates to the following curable compositions [1] to [9]. [1] A curable composition that contains a polymerizable compound and is cured by exposure to actinic radiation, the content of the monofunctional polymerizable compound having a melting point of 25° C. or lower is 5% by mass or more and 50% by mass or less based on the total mass of the polymerizable compound; The content of the polyfunctional polymerizable compound relative to the total mass of the polymerizable compound is 50% by mass or more and 95% by mass or less, The curable composition was applied to a substrate to form a coating film having an average thickness of 8 μm, and the coating film was then heated to 400 mJ / m 2 a curable composition, the composition being cured by exposure to actinic radiation, the cured film obtained satisfies both of the following conditions (1) and (2) when, using a nanoindentation evaluation device, the load required to press an indenter into the cured film by 100 nm in the thickness direction is defined as P1 and the load after maintaining the indented state for 2 seconds is defined as P2: (1) P2 is 20 μN or less (2) The relaxation rate calculated by the formula ((P1-P2) / P1×100) is 15% or more. [2] The cured film has a relaxation rate of 20% or more. The curable composition according to [1]. [3] The cured film has a P2 of 10 μN or less. The curable composition according to [1] or [2]. [4] The polymerizable compound includes a compound having a cyclic structure. The curable composition according to any one of [1] to [3]. [5] The polymerizable compound includes a compound having an aromatic ring. The curable composition according to any one of [1] to [4]. [6] The polymerizable compound includes a compound having a benzene ring. The curable composition according to any one of [1] to [5]. [7] The monofunctional polymerizable compound includes a monofunctional polymerizable compound having a melting point of 25° C. or less and a molecular weight of 280 or more. The curable composition according to any one of [1] to [6]. [8] Contains a gelling agent. The curable composition according to any one of [1] to [7]. [9] An inkjet ink. The curable composition according to any one of [1] to [8].

[0008] In order to solve the above problems, another aspect of the present invention relates to the following methods for producing a cured film

[10] to

[13] .

[10] A step of applying the curable composition according to any one of [1] to [9] to a surface of a substrate; curing the applied curable composition by irradiation with actinic radiation; The method for producing a cured film comprising the steps of:

[11] The curable composition is applied by an inkjet method. A method for producing a cured film according to

[10] .

[12] The temperature of the curable composition at the time of application is 60° C. or higher. A method for producing a cured film according to

[10] or

[12] .

[13] The amount of the actinic radiation irradiated is 600 mJ / cm 2 Below is the The method for producing a cured film according to any one of

[10] to

[12] . Effect of the Invention

[0009] According to the present invention, there are provided a curable composition capable of producing a cured film that is compatible with the ability to follow deformation of a substrate and suppresses cracking near the cut portion, in particular a cured film that suppresses changes in quality between substrates when multiple substrates are stacked and cut, and a method for producing a cured film using the same. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1A is a graph showing typical results when load measurement is performed using a nanoindentation evaluation device on a cured film formed from a conventional curable composition, FIG. 1B is a graph showing typical results when load measurement is performed using a nanoindentation evaluation device on a cured film with enhanced flexibility as described in Patent Document 1, and FIG. 1C is a graph showing typical results when load measurement is performed using a nanoindentation evaluation device on a cured film formed from the curable composition of the present embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing the configuration of an apparatus for producing a cured film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described in detail. However, the present invention is not limited to the following embodiment.

[0012] 1.Curable composition One embodiment of the present invention relates to a curable composition that contains a polymerizable compound that is polymerized by irradiation with actinic rays, and that is cured by polymerization of the polymerizable compound when irradiated with actinic rays.

[0013] 1-1. Polymerizable compounds The polymerizable compound may be a compound that is polymerized by irradiation with actinic radiation, and may be a radical polymerizable compound or a cationic polymerizable compound. Of these, radical polymerizable compounds are preferred. Examples of actinic radiation include electron beams, ultraviolet rays, α rays, γ rays, and X-rays. Of these, ultraviolet rays and electron beams are preferred, and ultraviolet rays are more preferred.

[0014] Examples of the first polymerizable compound as the radical polymerizable compound include unsaturated carboxylic acid ester and (meth)acrylate. Among these, (meth)acrylate is preferred. In this specification, "(meth)acrylate" means acrylate or methacrylate, and "(meth)acrylic" means acrylic or methacrylic.

[0015] The curable composition was applied to a substrate to form a coating film having an average thickness of 8 μm, and the coating film was then heated to 400 mJ / m 2 This composition, when cured by exposure to actinic radiation, gives a cured film that satisfies both of the following conditions (1) and (2), when the load required to indent the cured film by 100 nm in the thickness direction using a nanoindentation evaluation device is P1 and the load after maintaining the indented state for 2 seconds is P2: (1) The relaxation rate calculated by the formula ((P1-P2) / P1×100) is 15% or more. (2) P2 is 20 μN or less

[0016] As described in Patent Document 1, a curable composition containing a large amount of monofunctional monomer can increase the flexibility of a cured film formed from the composition. Therefore, such a composition can form a cured film with high conformity to a substrate. On the other hand, when the flexibility of the cured film is increased, cracks tend to occur near the cut portion when multiple substrates on which the cured film is formed are stacked and cut.

[0017] According to the findings of the present inventors, it is believed that continuous stress is generated in the cured film formed on the top substrate while the cutting blade is in contact with and pressed into the film. On the other hand, it is believed that large shear stress is instantaneously generated in the cured film formed on the second and subsequent substrates due to the movement of the cutting blade cutting the laminated cured film and substrates. In this way, the quality of the stress that causes breakage is different between the cured film formed on the top substrate and the cured film formed on the second and subsequent substrates, so that different breakages are likely to occur, and therefore it is believed that the quality of the cut portion is likely to differ.

[0018] In order to prevent cracking due to the above-mentioned continuous stress, it is desirable that the cured film formed on the top substrate has a degree of flexibility that allows it to easily deform in response to the pressure of the cutting blade, and that this deformation can relieve the above-mentioned stress.

[0019] In addition, the cured film formed on the second or subsequent substrates is desirably strong enough to withstand a momentary load in order to prevent cracking due to the momentary stress described above. In other words, in order to prevent cracking during cutting when formed on the second or subsequent substrates, the cured film desirably has a property that a large load is required (high strength) at the moment the cutting blade is pressed in.

[0020] These properties can be confirmed by using a nanoindentation evaluation device to press an indenter into the cured film and measure the amount of load when the indentation is maintained.

[0021] FIG. 1A is a graph showing a typical result of load measurement by a nanoindentation evaluation device on a cured film formed from a conventional curable composition, FIG. 1B is a graph showing a typical result of load measurement by a nanoindentation evaluation device on a cured film with enhanced flexibility as described in Patent Document 1, and FIG. 1C is a graph showing a typical result of load measurement by a nanoindentation evaluation device on a cured film formed from a curable composition according to the present embodiment. The horizontal axis of FIG. 1A to FIG. 1C indicates the time from when the indenter starts to be pressed, and the vertical axis indicates the load amount at that time. The time when the indenter is pressed 100 nm into the cured film is set to time X, and the time when the state of pressing the indenter 100 nm from time X is held for 2 seconds is set to time Y.

[0022] As shown in FIG. 1A, a cured film formed from a conventional curable composition has high strength, so the load P1 at time X is large, but the load P2 at time Y is also large. Such a cured film is difficult to relax stress ((P1-P2) is small), so when substrates on which a cured film is formed are stacked and cut, the cured film formed on the top substrate is likely to crack near the cut portion. In addition, such a cured film has a large P2 and low flexibility, so it is difficult to follow the deformation of the substrate and is likely to break during folding processing.

[0023] As shown in FIG. 1B, the cured film with enhanced flexibility has low load P1 at time X and low load P2 at time Y. Such a cured film is highly flexible (low P2), so it easily follows the deformation of the substrate and is less likely to break during folding. However, such a cured film is less likely to relax stress ((P1-P2) is small), so when substrates on which a cured film is formed are stacked and cut, cracks are likely to occur near the cut part in the cured film formed on the top substrate. In addition, since the strength of the cured film is low (small P1), it is easily broken by the shear stress caused by the cutting blade during cutting, and cracks are likely to occur in the cured film formed on the second and subsequent substrates.

[0024] In contrast, the curable composition according to the present embodiment can form a cured film with a high load P1 at time X and a low load P2 at time Y. Such a cured film is flexible (low P2), so it easily follows the deformation of the substrate and is less likely to break during folding. In addition, since the stress relaxation property is high ((P1-P2) is large), the cured film formed on the top substrate is less likely to crack. Furthermore, since the strength of the film is high (high P1), when the substrates on which the cured film is formed are stacked and cut, the cured film formed on the second and subsequent substrates is less likely to break due to the shear stress caused by the cutting blade during cutting, and is less likely to crack. Furthermore, a cured film with a high stress relaxation rate has high abrasion resistance.

[0025] Specifically, the cured film formed from the curable composition according to the present embodiment under the above conditions has a load P2 of 20 μN or less. The load P2 is preferably 10 μN or less, and more preferably 8 μN or less. The lower limit of P2 is not particularly limited, but can be 1 μN or more.

[0026] The cured film has a relaxation rate of 15% or more calculated by the formula ((P1-P2) / P1×100). The relaxation rate is preferably 20% or more, and more preferably 25% or more. The upper limit of the relaxation rate is not particularly limited, but can be 40% or less.

[0027] In this embodiment, the content of monofunctional polymerizable compounds having a melting point of 25°C or lower is 5% by mass or more and 50% by mass or less, and the content of polyfunctional polymerizable compounds is 50% by mass or more and 95% by mass or less, relative to the total mass of polymerizable compounds contained in the curable composition.

[0028] A monofunctional polymerizable compound having a melting point of 25°C or less makes the cured film flexible when polymerized, and reduces the load P2. This is believed to be because the polymerizable compound forms a side chain with low crystallinity when polymerized. This side chain exists in a mobile state in the cured film, and when a continuous load is applied to the cured film, it moves in the cured film and takes a stable state according to the direction of the load. This movement of the side chain causes the cured film to deform while relieving stress. Therefore, the polymerizable compound can increase the relaxation rate of the cured film and reduce P2.

[0029] On the other hand, the polyfunctional polymerizable compound increases the strength of the cured film and increases the load P1. The monofunctional polymerizable compound having a melting point of 25° C. or less reduces the load P2, and the polyfunctional polymerizable compound increases P1, so that it is believed that a cured film that satisfies both of the above conditions (1) and (2) can be obtained.

[0030] From the viewpoint of achieving a balance between these, the content of the monofunctional polymerizable compound having a melting point of 25° C. or lower is preferably 10% by mass to 60% by mass, more preferably 20% by mass to 40% by mass, based on the total mass of the polymerizable compounds, and the content of the polyfunctional polymerizable compound is preferably 20% by mass to 90% by mass, more preferably 40% by mass to 70% by mass.

[0031] Examples of monofunctional polymerizable compounds having a melting point of 25° C. or less include 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl acrylate, isobutyl acrylate, t-butyl acrylate, isooctyl acrylate, 2-methoxyethyl acrylate, methoxytriethylene glycol acrylate, 2-ethoxyethyl acrylate, 3-methoxybutyl acrylate, ethoxyethyl acrylate, butoxyethyl acrylate, ethoxydiethylene glycol acrylate, methoxydipropylene glycol acrylate, dipropylene glycol acrylate, β-carboxyethyl acrylate, ethyl diglycol acrylate, trimethylolpropane formal monoacrylate, imide acrylate, isoamyl acrylate, ethoxylated succinic acid acrylate, trifluoro acrylate, ethyl ... Examples of the acrylate acrylate include arylethyl acrylate, ω-carboxypolycaprolactone monoacrylate, N-vinylformamide, cyclohexyl acrylate, tetrahydrofurfuryl acrylate, benzyl acrylate, methylphenoxyethyl acrylate, 4-t-butylcyclohexyl acrylate, caprolactone-modified tetrahydrofurfuryl acrylate, tribromophenyl acrylate, ethoxylated tribromophenyl acrylate, 2-phenoxyethyl acrylate (or its ethylene oxide or propylene oxide addition monomer), acryloylmorpholine, isobornyl acrylate, phenoxydiethylene glycol acrylate, vinyl caprolactam, vinyl pyrrolidone, 2-hydroxy-3-phenoxypropyl acrylate, and 1,4-cyclohexanedimethanol monoacrylate.

[0032] From the viewpoint of forming a low crystallinity and mobile moiety in the side chain to make the cured film more flexible (to lower P2), the monofunctional polymerizable compound preferably contains a monofunctional polymerizable compound having a melting point of 25° C. or less and a molecular weight of 280 or more. In addition, by increasing the proportion of such monofunctional polymerizable compounds having a relatively large molecular weight, the scratch resistance of the cured film can be improved and the continuous ejection stability when ejecting the curable composition from an inkjet head can also be improved. The monofunctional polymerizable compound preferably has a molecular weight of 300 or more. The upper limit of the molecular weight is not particularly limited, but can be 1000 or less.

[0033] The content of the monofunctional polymerizable compound having a melting point of 25° C. or lower and a molecular weight of 280 or higher is preferably 10% by mass or more and 60% by mass or less, and more preferably 20% by mass or more and 40% by mass or less, based on the total mass of the polymerizable compounds.

[0034] Examples of the polyfunctional polymerizable compound include triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, and hydroxypivalic acid neopentyl glycol di(meth)acrylate. Examples of the acrylates include difunctional (meth)acrylates such as trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, glycerin propoxy tri(meth)acrylate, and pentaerythritol ethoxy tetra(meth)acrylate.

[0035] From the viewpoint of forming a mobile site with low crystallinity in the cured film to make the cured film more flexible (to lower P2), the polymerizable compound is preferably a compound having a cyclic structure. The type of the cyclic structure is not particularly limited, and may be an alicyclic or aromatic ring, but is preferably an aromatic ring, and more preferably a benzene ring. The polymerizable compound having a cyclic structure may be a monofunctional polymerizable compound or a polyfunctional polymerizable compound. Among these, from the viewpoint of forming a mobile cyclic structure in the side chain to further enhance stress relaxation, a monofunctional polymerizable compound is preferred.

[0036] Examples of the polymerizable compound having a cyclic structure include phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, cumylphenoxylethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, isobornyl (meth)acrylate, (5-ethyl-1,3-dioxane-5-yl)methyl (meth)acrylate, cyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, and N-vinyl caprolactam.

[0037] The content of the polymerizable compound having a cyclic structure is preferably from 10% by mass to 60% by mass, and more preferably from 20% by mass to 40% by mass, based on the total mass of the polymerizable compounds.

[0038] The polymerizable compound may include a monofunctional polymerizable compound having a melting point higher than 25° C. Examples of the monofunctional polymerizable compound having a melting point higher than 25° C. include octadecyl (meth)acrylate, tris(2-(meth)acryloyloxyethyl)isocyanurate, stearyl (meth)acrylate, behenyl (meth)acrylate, and the like.

[0039] From the viewpoint of lowering the load P2 of the cured film, the content of the monofunctional polymerizable compound having a melting point higher than 25° C. is preferably less than 3 mass %, more preferably less than 1 mass %, and even more preferably less than 0.1 mass %, based on the total mass of the polymerizable compounds.

[0040] The content of the polymerizable compound can be from 1 mass % to 97 mass % inclusive, preferably from 30 mass % to 95 mass % inclusive, more preferably from 50 mass % to 95 mass % inclusive, and even more preferably from 70 mass % to 95 mass % inclusive, relative to the total mass of the curable composition.

[0041] 1-2.Other ingredients The curable composition may further contain other ingredients such as polymerization initiators, gelling agents, pigments, dyes, surfactants, optical brighteners, and polymerization inhibitors.

[0042] The polymerization initiator may be any compound that initiates polymerization of the polymerizable compound by irradiation with actinic rays. For example, when the polymerizable compound has a radical polymerizable compound, the polymerization initiator can be a radical polymerization initiator, and when the polymerizable compound has a cationic polymerizable compound, the polymerization initiator can be a cationic polymerization initiator (photoacid generator). Note that, when the curable composition can be sufficiently cured without the polymerization initiator, such as when the curable composition is cured by irradiation with electron beams, the polymerization initiator is not required.

[0043] The radical polymerization initiator may be an intramolecular bond cleavage type radical polymerization initiator, or an intramolecular hydrogen abstraction type radical polymerization initiator.

[0044] Examples of the intramolecular bond cleavage type radical polymerization initiator include acetophenone-based initiators including diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyl dimethyl ketal, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexyl-phenyl ketone, 2-methyl-2-morpholino(4-methylthiophenyl)propan-1-one, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone, benzoins including benzoin methyl ether, and benzoin isopropyl ether, acylphosphine oxide-based initiators including 2,4,6-trimethylbenzoin diphenylphosphine oxide, and benzyl and methylphenyl glyoxyesters.

[0045] Examples of the intramolecular hydrogen abstraction type radical polymerization initiator include benzophenone-based initiators including benzophenone, o-benzoylmethylbenzoate, 4-phenylbenzophenone, 4,4'-dichlorobenzophenone, hydroxybenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, acrylated benzophenone, 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone, and 3,3'-dimethyl-4-methoxybenzophenone; thioxanthone-based initiators including 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, and 2,4-dichlorothioxanthone; aminobenzophenone-based initiators including Michler's ketone and 4,4'-diethylaminobenzophenone; 10-butyl-2-chloroacridone, 2-ethylanthraquinone, 9,10-phenanthrenequinone, and camphorquinone.

[0046] Examples of cationic polymerization initiators include photoacid generators. Examples of photoacid generators include aromatic onium compounds such as diazonium, ammonium, iodonium, sulfonium, and phosphonium, such as B(C6F5)4. - , PF6 - , AsF6 - , SbF6 - , CF3SO3 - These include salts, sulfonates which generate sulfonic acids, halides which photogenerate hydrogen halides, and iron-allene complexes.

[0047] The content of the polymerization initiator is not particularly limited as long as the curable composition is sufficiently cured by irradiation with actinic rays (e.g., ultraviolet rays). For example, the content of the polymerization initiator is preferably 0.1% by mass or more and 20% by mass or less, more preferably 1% by mass or more and 10% by mass or less, based on the total mass of the curable composition.

[0048] The gelling agent is a compound that makes the curable composition gel at room temperature (25°C) and sol when heated (e.g., 80°C). For example, the gelling agent is preferably a compound that dissolves in the liquid components (polymerizable compound, organic solvent, etc.) contained in the curable composition at a temperature higher than the gelling temperature of the curable composition and crystallizes at a temperature lower than the gelling temperature of the curable composition. The gelling temperature means a temperature at which the curable composition undergoes a phase transition from sol to gel and the viscosity of the curable composition suddenly changes when the curable composition that has been solated or liquefied by heating is cooled. Specifically, the temperature at which the viscosity suddenly increases when the solated or liquefied curable composition is cooled while measuring the viscosity with a rheometer (e.g., MCR300, manufactured by Anton Paar) can be regarded as the gelling temperature of the curable composition.

[0049] The gelling agent can increase the flexibility of the cured film and reduce the load P2, thereby increasing (P1-P2) and improving the stress relaxation of the cured film.

[0050] The gelling agent preferably crystallizes in the curable composition at a temperature equal to or lower than the gelling temperature of the curable composition, and forms a structure in which the polymerizable compound is encapsulated in a three-dimensional space formed by the gelling agent crystallized into a plate shape (such a structure is hereinafter referred to as a "house of card structure"). A gelling agent that forms a house of card structure can make the cured film less likely to break during folding or other processes. In addition, a gelling agent that forms a house of card structure can form a cured film that has improved pinning properties when the curable composition is applied to a substrate by an inkjet method, and is patterned more finely or has dots arranged with high resolution.

[0051] Examples of gelling agents that tend to form a house-of-cards structure include aliphatic ketones, aliphatic esters, petroleum-based waxes, vegetable waxes, animal waxes, mineral waxes, hydrogenated castor oil, modified waxes, higher fatty acids, higher alcohols, hydroxystearic acid, fatty acid amides including N-substituted fatty acid amides and special fatty acid amides, higher amines, esters of sucrose fatty acids, synthetic waxes, dibenzylidene sorbitol, dimer acid and dimer diol.

[0052] Examples of aliphatic ketones include dilignoceryl ketone, dibehenyl ketone, distearyl ketone, dieicosyl ketone, dipalmityl ketone, dilauryl ketone, dimyristyl ketone, myristyl palmityl ketone, and palmityl stearyl ketone.

[0053] Examples of fatty esters include fatty acid esters of monoalcohols such as behenyl behenate, icosanoic acid ethyl ester, stearyl stearate, palmityl stearate, myristyl myristate, cetyl myristate, and oleyl palmitate; and fatty acid esters of polyhydric alcohols such as glycerin fatty acid esters, sorbitan fatty acid esters, propylene glycol fatty acid esters, ethylene glycol fatty acid esters, and polyoxyethylene fatty acid esters.

[0054] Commercially available examples of the above aliphatic esters include the EMALEX series (manufactured by Nippon Emulsion Co., Ltd. ("EMALEX" is a registered trademark of the company)), the Rikemal series, and the Poem series (manufactured by Riken Vitamin Co., Ltd. ("Rikemal" and "Poem" are both registered trademarks of the company)).

[0055] Examples of higher fatty acids include behenic acid, arachidic acid, stearic acid, palmitic acid, myristic acid, lauric acid, oleic acid, and erucic acid.

[0056] Examples of higher alcohols include stearyl alcohol and behenyl alcohol.

[0057] Among these, from the viewpoint of forming a strong card house structure and making it difficult to break during folding etc., the gelling agent is preferably an aliphatic ketone, an aliphatic ester, a higher fatty acid, or a higher alcohol, and more preferably an aliphatic ketone represented by the following general formula (G1) or an aliphatic ester represented by the following general formula (G2). Only one type of gelling agent may be contained, or two or more types may be contained in combination.

[0058] General formula (G1):R a -CO-R b General formula (G2):R c -COO-R d

[0059] R in general formula (G1) a and R b each independently represents a linear hydrocarbon group having 12 to 26 carbon atoms, which may have a branched chain, and R in general formula (G2) c and R d each independently represents a linear hydrocarbon group having 12 to 26 carbon atoms, which may have a branched chain.

[0060] The gelling agents shown in general formulas (G1) and (G2) are represented by R a ~R d Since the number of carbon atoms is 12 or more, the crystallinity is high and a sufficiently large space is generated inside the house-of-cards structure, so that the effect of improving the resistance to fold cracking by including the polymerizable compound (A) is more sufficiently exhibited.

[0061] The gelling agents shown in general formulas (G1) and (G2) are represented by R a ~R d Since the carbon number of is 26 or less, the melting point is appropriately low and the soling temperature of the curable composition when made into an inkjet ink is not too high, so that the heating temperature of the inkjet ink during ejection can be made low.

[0062] Examples of aliphatic ketones represented by general formula (G1) include dilignoceryl ketone (carbon number: 23-24), dibehenyl ketone (carbon number: 21-22), distearyl ketone (carbon number: 17-18), dieicosyl ketone (carbon number: 19-20), dipalmityl ketone (carbon number: 15-16), dimyristyl ketone (carbon number: 13-14), dilauryl ketone (carbon number: 11-12), lauryl ketone (carbon number: 13-14), and glyceryl ketone (carbon number: 14-16). These include myristyl ketone (carbon number: 11-14), lauryl palmityl ketone (11-16), myristyl palmityl ketone (13-16), myristyl stearyl ketone (13-18), myristyl behenyl ketone (13-22), palmityl stearyl ketone (15-18), palmityl behenyl ketone (15-22) and stearyl behenyl ketone (17-22). The number of carbon atoms in the parentheses above indicates the number of carbon atoms in each of the two hydrocarbon groups separated by the carbonyl group.

[0063] Examples of commercially available products of the compound represented by general formula (G1) include 18-Pentatriacontanone and Hentriacontan-16-one (both manufactured by Alfa Aeser), and Kaowax T1 (manufactured by Kao Corporation).

[0064] Examples of the aliphatic ester represented by the general formula (G2) include behenyl behenate (carbon number: 21-22), icosanoic acid icosyl (carbon number: 19-20), stearyl stearate (carbon number: 17-18), palmityl stearate (carbon number: 17-16), lauryl stearate (carbon number: 17-12), cetyl palmitate (carbon number: 15-16), stearyl palmitate (carbon number: 15-18), myristyl Myristyl phosphate (carbon number: 13-14), cetyl myristate (carbon number: 13-16), octyldodecyl myristate (carbon number: 13-20), stearyl oleate (carbon number: 17-18), stearyl erucate (carbon number: 21-18), stearyl linoleate (carbon number: 17-18), behenyl oleate (carbon number: 18-22), and arachidyl linoleate (carbon number: 17-20). The number of carbons in the parentheses above indicates the number of carbons in each of the two hydrocarbon groups separated by the ester group.

[0065] Examples of commercially available aliphatic esters represented by general formula (G2) include Unistar M-2222SL, Sperm Acetate, Nissan Electol WEP-2 and Nissan Electol WEP-3 (all manufactured by NOF Corp., "Unistar" and "Nissan Electol" are both registered trademarks of the company), Exepar SS and Exepar MY-M (all manufactured by Kao Corp., "Exepar" is a registered trademark of the company), EMALEX CC-18 and EMALEX CC-10 (manufactured by Nippon Emulsion Co., Ltd., "EMALEX" is a registered trademark of the company), and Amureps PC (manufactured by Kokyu Alcohol Kogyo Co., Ltd., "Amureps" is a registered trademark of the company). These commercially available products are often mixtures of two or more types, so they may be separated and purified as necessary before being included in the curable composition.

[0066] The content of the gelling agent is preferably 0.5% by mass or more and 10% by mass or less, more preferably 0.5% by mass or more and 8% by mass or less, and even more preferably 1% by mass or more and 6% by mass or less, based on the total mass of the curable composition. The higher the content of the gelling agent, the more difficult it is for the cured film to break during folding or the like, and the more the pinning ability of the curable composition can be improved.

[0067] Examples of pigments include known red pigments, yellow pigments, blue pigments, black pigments, white pigments, etc. Examples of dyes include known red dyes, yellow dyes, black dyes, blue dyes, etc.

[0068] Examples of surfactants include anionic surfactants such as dialkyl sulfosuccinates, alkyl naphthalene sulfonates, and fatty acid salts; nonionic surfactants such as polyoxyethylene alkyl ethers, polyoxyethylene alkyl allyl ethers, acetylene glycols, and polyoxyethylene-polyoxypropylene block copolymers; cationic surfactants such as alkylamine salts and quaternary ammonium salts; and silicone-based and fluorine-based surfactants.

[0069] The content of the surfactant is not particularly limited, but can be, for example, 0.001% by mass or more and less than 1.0% by mass relative to the total mass of the curable composition.

[0070] Examples of the polymerization inhibitor include N-oxyl-based polymerization inhibitors, phenol-based polymerization inhibitors, quinone-based polymerization inhibitors, amine-based polymerization inhibitors, copper dithiocarbamate-based polymerization inhibitors, etc. The polymerization inhibitor may be contained in the curable composition alone or in combination of two or more kinds.

[0071] Examples of N-oxyl polymerization inhibitors include 4-hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl (TEMPO), 4-hydroxy-2,2,6,6-tetramethyl-piperidine-N-oxyl, 4-oxo-2,2,6,6-tetramethyl-piperidine-N-oxyl, 4-methoxy-2,2,6,6-tetramethyl-piperidine-N-oxyl, 4-acetoxy-2,2,6,6-tetramethyl-piperidine-N-oxyl, etc. Examples of commercially available N-oxyl polymerization inhibitors include Irgastab UV10 (manufactured by BASF ("Irgastab" is a registered trademark of the company)).

[0072] Examples of the phenol-based polymerization inhibitor include 2,6-di-tert-butylphenol, 2,4-di-tert-butylphenol, 2-tert-butyl-4,6-dimethylphenol, 2,6-di-tert-butyl-4-methylphenol, 2,4,6-tri-tert-butylphenol, 2,6-di-t-butyl-p-cresol (butylated hydroxytoluene: BHT), 4-methoxyphenol, 2-methoxy-4-methylphenol, and the like.

[0073] Examples of the quinone polymerization inhibitor include hydroquinone, methoxyhydroquinone, benzoquinone, 1,4-naphthoquinone, and p-tert-butylcatechol.

[0074] Examples of amine-based polymerization inhibitors include alkylated diphenylamines, N,N'-diphenyl-p-phenylenediamine, phenothiazine, and the like.

[0075] Examples of the copper dithiocarbamate polymerization inhibitor include copper dimethyldithiocarbamate, copper diethyldithiocarbamate, copper dibutyldithiocarbamate, and the like.

[0076] The content of the polymerization inhibitor is not particularly limited, but can be, for example, from 0.01% by mass to 0.5% by mass relative to the total mass of the curable composition.

[0077] 1-3. Physical properties of the curable composition The curable composition may be an inkjet ink that can be ejected from the nozzles of an inkjet head, or a composition that can be applied to a substrate by a method such as a dispenser, a bar coater, a screen roller, or spray application.

[0078] In the case of an inkjet ink, the viscosity of the curable composition at 60° C. is preferably 10 mPa·s or more and 25 mPa·s or less, which can improve the ejection properties when the ink is heated and ejected from an inkjet head.

[0079] The viscosity can be measured by a rheometer. For example, the precoat agent is heated to 100°C, and while measuring the viscosity by a stress-controlled rheometer (Physica MCR301 (diameter of cone plate: 75 mm, cone angle: 1.0°), the ink is cooled to 20°C under conditions of a shear rate of 11.7 (1 / s) and a temperature drop rate of 0.1°C / s to obtain a temperature change curve of the viscosity. The viscosity can be obtained by reading the viscosity at 80°C from the obtained temperature change curve.

[0080] 1-4. Method for preparing curable composition The curable composition can be prepared by mixing the above-mentioned polymerizable compound and other components under heating. At this time, it is preferable to filter the obtained mixture with a predetermined filter. When preparing a curable composition containing a pigment, it is preferable to prepare a pigment dispersion containing a pigment and a polymerizable compound, and then mix the pigment dispersion with other components. The pigment dispersion may further contain a dispersant.

[0081] The pigment dispersion can be prepared by dispersing a pigment in a polymerizable compound using, for example, a ball mill, a sand mill, an attritor, a roll mill, an agitator, a Henschel mixer, a colloid mill, an ultrasonic homogenizer, a pearl mill, a wet jet mill, a paint shaker, or the like.

[0082] 2. Image forming method The above-mentioned curable composition can be used for forming a cured film by applying the curable composition to a substrate and then curing the applied curable composition by irradiation with actinic rays.

[0083] The method of application to the substrate is not limited, and can be various methods such as bar coating, spray coating, curtain coating, roll coating, screen printing, offset printing, gravure printing, dispenser method, inkjet method, etc. Among these, the inkjet method is preferred because it is easy to form fine patterns and high-definition images.

[0084] In the inkjet method, the ejection method from the inkjet head may be either an on-demand method or a continuous method. The on-demand inkjet head may be either an electro-mechanical conversion type such as a single cavity type, a double cavity type, a bender type, a piston type, a share mode type, or a shared wall type, or an electro-thermal conversion type such as a thermal inkjet type or a bubble jet type ("bubble jet" is a registered trademark of Canon Inc.). In addition, the inkjet head may be either a scan type or a line type.

[0085] The curable composition is preferably heated and applied to the substrate. The heating temperature is not particularly limited, but may be 60° C. or higher. When the curable composition contains a gelling agent, the heating temperature is preferably a temperature at which the curable composition is converted into a sol, and more preferably a temperature at least 10° C. above the gelling temperature and not more than 30° C. above the gelling temperature. When the curable composition is applied to the substrate by an inkjet method, the heating temperature may be the temperature at the time of ejection from an inkjet head.

[0086] The substrate is not particularly limited, and various substrates such as paper, plastic, resin, and metal can be used. Examples of the paper that can be used include ordinary uncoated paper, coated paper, and synthetic paper such as Yupo (Yupo is a registered trademark of Yupo Corporation). Examples of the plastic that can be used include films such as PP film, PET film, OPS film, OPP film, ONy film, PVC film, PE film, and TAC film, as well as molded bodies such as polycarbonate, (meth)acrylic resin, ABS, polyacetal, PVA, and rubber. These plastics may be films used for soft packaging.

[0087] The curable composition may be applied directly to the substrate, or may be applied to an intermediate transfer member and then transferred from the intermediate transfer member to the substrate.

[0088] The actinic radiation irradiated to the curable composition applied to the substrate may be an electron beam, an ultraviolet ray, an α-ray, a γ-ray, an X-ray, etc., and is preferably an ultraviolet ray or an electron beam. The ultraviolet ray is preferably a light having a peak wavelength of 360 nm or more and 410 nm or less. The ultraviolet ray is preferably irradiated from an LED light source. LEDs emit less radiant heat than conventional light sources (e.g., metal halide lamps, etc.). Therefore, when the LED is irradiated with actinic radiation, the curable composition is less likely to melt and is less likely to cause uneven gloss.

[0089] The cumulative amount of actinic radiation irradiated is 100 mJ / cm 2 More than 1000mJ / cm 2 The curable composition has good curability. Therefore, the integrated light amount is 600 mJ / cm or less. 2 can be less than 100 mJ / cm 2 More than 600mJ / cm 2 By reducing the integrated amount of light, the curable composition can be cured in a short time, which makes it easier to handle high-speed printing of images by, for example, an inkjet method.

[0090] 3. Hardened film forming equipment Fig. 2 is a schematic diagram showing the configuration of an apparatus 100 for forming a cured film using the above-mentioned curable composition. As shown in Fig. 2, the apparatus 100 has an application section 110 for applying the curable composition to a substrate, a transport section 120, and an irradiation section 130. The apparatus 100 shown in Fig. 2 is an example of an image forming apparatus for forming an image by an inkjet method, and the application section 110 is an inkjet head. In Fig. 2, an arrow indicates the transport direction of the substrate.

[0091] The application unit 110, which is an inkjet head, has a nozzle surface 113 on which an outlet of a nozzle 111 is provided, on a surface facing the transport unit 120, and discharges the curable composition onto the substrate 200 transported by the transport unit 120. From the viewpoint of improving the dischargeability of the curable composition, the application unit 110 may have a temperature adjustment means for adjusting the temperature of the curable composition to adjust the viscosity of the curable composition to a low level. Examples of the temperature adjustment means include a panel heater, a ribbon heater, and a heating means using warm water. The heating temperature is, for example, 60° C. or higher.

[0092] The application unit 110 may be a scanning type inkjet head whose width in a direction perpendicular to the substrate transport direction is smaller than that of the substrate 200, or a line type inkjet head whose width in a direction perpendicular to the substrate transport direction is larger than that of the substrate 200.

[0093] The nozzles 111 have ejection openings on a nozzle surface 113. The number of nozzles 111 may be equal to or greater than the number of inks used in image formation (for example, four).

[0094] When forming an image, the conveying unit 120 conveys the substrate 200 such that the substrate 200 facing the application unit 110 moves directly below the application unit 110 in the vertical direction. For example, the conveying unit 120 includes a drive roller 121, a driven roller 122, and a conveying belt 123.

[0095] The irradiation unit 130 irradiates the upper surface of the transport unit 120 with active rays. This allows droplets of the active ray-curable inkjet ink that have landed on the transported substrate 200 to be irradiated with active rays, thereby curing the droplets. The irradiation unit 130 can be disposed immediately above the transport unit 120, downstream of the application unit 110. In this embodiment, the irradiation unit 130 is an LED that irradiates ultraviolet rays. The light amount of the irradiation unit 130 is set so that the integrated light amount of the active rays irradiated to the curable composition is 100 mJ / cm. 2 More than 1000mJ / cm 2 Less than 100 mJ / cm 2 More than 600mJ / cm 2 The amount can be as follows:

[0096] In addition to the above configuration, the device 100 may also have an ink tank (not shown) for storing actinic ray-curable ink before ejection, an ink flow path (not shown) that connects the ink tank and the deposition unit 110 so that the ink can flow therethrough, and a control unit (not shown) that controls the operation of the deposition unit 110, the transport unit 120, and the irradiation unit 130.

[0097] The device 100 may also have an intermediate transfer body and a transfer unit (neither shown). At this time, the application unit 110 ejects actinic ray curable inkjet ink onto the intermediate transfer body, causing it to land on the surface of the intermediate transfer body, and forms an intermediate image on the surface of the intermediate transfer body, which is made up of droplets of the actinic ray curable inkjet ink. Thereafter, the transfer unit transfers the intermediate image from the surface of the intermediate transfer body to the surface of the substrate. Then, the irradiation unit 130 irradiates the intermediate image transferred to the surface of the substrate with actinic rays, thereby curing the droplets of the actinic ray curable inkjet ink. EXAMPLES

[0098] The present invention will now be described with reference to examples, which should not be construed as limiting the scope of the present invention.

[0099] 1. Preparation / synthesis of materials The materials used in preparing the curable compositions are listed below.

[0100] 1-1. Pigment dispersion 9 parts by mass of a pigment dispersant (EFKA-7701, manufactured by BASF) and 71 parts by mass of tripropylene glycol diacrylate were placed in a stainless steel beaker and heated and stirred for 1 hour while being heated to 65°C on a hot plate. Then, the mixture was cooled to room temperature, and 20 parts by mass of the pigment described below was added to the stainless steel beaker after stirring, and the mixture was then placed in a glass bottle together with 200 g of zirconia beads (diameter 0.3 mm, manufactured by Nikkato Corporation) and sealed. This pigment-containing liquid was subjected to a dispersion treatment for 4 hours using a paint shaker, and the zirconia beads were removed to obtain a pigment dispersion liquid. Cyan pigment: Pigment Blue 15:4 (Chromofine Blue 6332JC, manufactured by Dainichi Seika Color & Chemicals Co., Ltd.)

[0101] 1-2.Polymerizable compound (Monofunctional polymerizable compound) m1:4EO modified phenyl acrylate m2: 4EO modified nonylphenol acrylate m3: (5-ethyl-1,3-dioxane-5-yl)methyl acrylate m4: 2-phenoxyethyl acrylate m5: stearyl acrylate

[0102] (Polyfunctional polymerizable compound) M1: Tripropylene glycol diacrylate M2: Polyethylene glycol #400 diacrylate M3: 9EO modified trimethylolpropane triacrylate M4: 3EO modified trimethylolpropane triacrylate

[0103] 1-3. Gelling agents G1: Behenyl stearate G2: Stearnon

[0104] 1-4. Photopolymerization initiator Initiator 1 (Omnirad TPO-L, IGM Resins BV) Initiator 2 (Speedcure 2-ITX, Arkema)

[0105] 1-5. Polymerization inhibitors Irgasutab UV-10 (manufactured by BASF)

[0106] 1-6.Surfactants KF-352A (Shin-Etsu Chemical Co., Ltd.)

[0107] 2. Preparation of Curable Composition The above materials were placed in a stainless steel beaker in the proportions shown in Tables 1 to 3, and stirred at 105° C. for 45 minutes. The mixture was then filtered through a 3 μm Teflon (registered trademark) membrane filter manufactured by ADVANTEC Corporation to obtain Curable Composition 1, which is an actinic radiation-curable inkjet ink. Curable Compositions 2 to 18 were obtained in the same manner, except that the types and amounts of the materials were changed.

[0108] [Table 1]

[0109] [Table 2]

[0110] [Table 3]

[0111] 3. Evaluation Nanoindentation evaluation was performed by the following method for Curable Compositions 1 to 18. In addition, cracks during folding and cutting, abrasion resistance, and continuous discharge stability were evaluated according to the following criteria.

[0112] The coating was formed using an inkjet head manufactured by Konica Minolta with 1776 nozzles, with a resolution of 600 dpi. The applied voltage was adjusted so that the droplet volume was 3.5 pl and the droplet speed was 6 m / sec, and two heads were arranged in a staggered pattern to record an image with a resolution of 1200 dpi x 1200 dpi. dpi refers to the number of dots per 2.54 cm. The image was formed in an environment of 23°C and 55% RH.

[0113] 3-1. Nanoindentation evaluation For each of the curable compositions 1 to 18, a coating film having an average thickness of 8 μm was formed on 127.9 g of Oji Paper OK Topcoat+ A3Y. This coating film was irradiated with a wavelength of 395 nm and an accumulated light amount of 400 mJ / m 2The cured film was obtained by irradiating the cured film with ultraviolet light of 100 nm. The cured film was left in an environment of 25°C and 60% RH for 24 hours. Then, the cured film was indented 100 nm in the thickness direction using a nanoindentation evaluation device (Triscope Hysitron, 90° Cube Corner Tip indenter). The load required to indent the cured film was P1, and the load after the indented state was maintained for 2 seconds was P2.

[0114] 3-2. Cracks during folding Similarly, for each of Curable Compositions 1 to 18, a coating film having an average thickness of 8 μm was formed on 127.9 g of Oji Paper OK Topcoat+ A3Y. This coating film was then irradiated with a light having a wavelength of 395 nm and an accumulated light amount of 400 mJ / m 2 The cured film was then left to stand for 24 hours in an environment of 25°C and 60% RH. Thereafter, the printed matter was folded in half (mountain fold) and the degree of cracking at the folded portion was visually evaluated. A: No cracks and no white background exposure B: There are cracks, but only a small amount of white background is exposed. C: Cracks and white background exposed in half the area D: Cracks and white background exposed over the entire area

[0115] 3-3.Cracks during cutting Similarly, for each of Curable Compositions 1 to 18, a coating film having an average thickness of 8 μm was formed on 127.9 g of Oji Paper OK Topcoat+ A3Y. This coating film was then irradiated with a light having a wavelength of 395 nm and an accumulated light amount of 400 mJ / m 2 The cured film was then irradiated with ultraviolet light of 1000 W to obtain a cured film. The obtained cured film was left in an environment of 25°C and 60% RH for 24 hours. After that, 10 printed sheets were cut by stacking them using an automatic cutter PC-P430 manufactured by Horizon Co., Ltd., and the cut parts were rubbed with a finger, and the degree of peeling of the first, fifth, and tenth sheets was visually evaluated. A: No peeling B: Peeling is present but difficult to see C: Peeling is visible D: Large peeling that is clearly visible

[0116] 3-4. Scratch resistance Similarly, for each of Curable Compositions 1 to 18, a coating film having an average thickness of 8 μm was formed on 127.9 g of Oji Paper OK Topcoat+ A3Y. This coating film was then irradiated with a light having a wavelength of 395 nm and an accumulated light amount of 400 mJ / m 2 The cured film was then left for 24 hours in an environment of 25°C and 60% RH. 2 The surface of the cured film was rubbed back and forth 10 times with an unprinted paper surface under a load of 1000 g. After rubbing, the rubbed paper surface and the unprinted paper surface were visually evaluated. A: No change on the rubbed paper surface, no color transfer to unprinted paper surface B: The rubbed paper surface is scratched, but there is no color transfer to the unprinted paper surface. C: Slight color transfer to unprinted paper D: Color transfer to unprinted paper to the extent that a decrease in color density is observed

[0117] 3-5.Continuous discharge stability The image output of each sample was visually checked for white streaks (white streaks due to poor ejection) in the 100% printed area when the 10th and 100th sheets were printed. A: No white spots B: There are one or two white spots, but it is not a problem for practical use. C: Many white spots occur

[0118] Tables 4 to 6 show the amounts of monofunctional polymerizable compounds and polyfunctional polymerizable compounds in Curable Compositions 1 to 18, the relaxation rates ((P1-P2) / P1x100) calculated from the load amounts P1 and P2 obtained in the nanoindentation evaluation, and the P2 values, as well as the evaluation results for cracking during folding and cutting, abrasion resistance, and continuous discharge stability.

[0119] [Table 4]

[0120] [Table 5]

[0121] [Table 6]

[0122] From the results of curable compositions 1 to 18, it can be seen that curable compositions in which the content of monofunctional polymerizable compounds having a melting point of 25°C or less is 5% by mass or more and 50% by mass or less, the content of polyfunctional polymerizable compounds is 50% by mass or more and 95% by mass or less, the P2 of the cured film measured by a nanoindentation evaluation device is 20 μN or less, and the relaxation rate calculated by the formula ((P1-P2) / P1×100) is 15% or more, are less likely to crack during folding and also are less likely to crack during cutting. [Industrial Applicability]

[0123] The curable composition of the present invention can produce a cured film that is compatible with the deformation of the substrate and suppresses cracking near the cut portion, particularly a cured film that suppresses changes in quality between substrates when multiple substrates are stacked and cut. Therefore, the present invention is useful in the field of image formation. [Explanation of symbols]

[0124] 100 devices 110 Granting Department 120 Conveyor 130 Irradiation unit 200 Base material

Claims

1. A curable composition which contains a polymerizable compound and is cured by exposure to actinic radiation, the content of the monofunctional polymerizable compound having a melting point of 25° C. or lower is 5% by mass or more and 50% by mass or less based on the total mass of the polymerizable compound; The content of the polyfunctional polymerizable compound relative to the total mass of the polymerizable compounds is 50% by mass or more and 95% by mass or less, The curable composition was applied to a substrate to form a coating film having an average thickness of 8 μm, and the coating film was exposed to an integrated light dose of 400 mJ / m 2 a curable composition, wherein a cured film obtained by curing the composition by exposure to actinic radiation satisfies both of the following conditions (1) and (2), when a load required to press an indenter into the cured film by 100 nm in a thickness direction using a nanoindentation evaluation device is defined as P1 and a load after maintaining the indented state for 2 seconds is defined as P2: (1) P2 is 20 μN or less (2) The relaxation rate calculated by the formula ((P1-P2) / P1×100) is 15% or more.

2. The cured film has a relaxation rate of 20% or more. The curable composition of claim 1.

3. The cured film has a P2 of 10 μN or less. The curable composition of claim 1.

4. The polymerizable compound includes a compound having a cyclic structure. The curable composition of claim 1.

5. The polymerizable compound includes a compound having an aromatic ring. The curable composition of claim 1.

6. The polymerizable compound includes a compound having a benzene ring. The curable composition of claim 1.

7. The monofunctional polymerizable compound includes a monofunctional polymerizable compound having a melting point of 25° C. or lower and a molecular weight of 280 or higher. The curable composition of claim 1.

8. Contains a gelling agent, The curable composition of claim 1.

9. Inkjet ink, The curable composition of claim 1.

10. Applying the curable composition according to any one of claims 1 to 9 to a surface of a substrate; curing the applied curable composition by irradiation with actinic radiation; The method for producing a cured film comprising the steps of:

11. The application of the curable composition is carried out by an inkjet method. A method for producing the cured film according to claim 10.

12. The temperature of the curable composition at the time of application is 60° C. or higher. A method for producing the cured film according to claim 10.

13. The amount of the actinic radiation irradiated is 600 mJ / cm 2 Below is the A method for producing the cured film according to claim 10.

Citation Information

Patent Citations

  • Active energy ray-curable composition

    JP2016172841A